Initial Phase and Modulation Factor Optimization for Structured Illumination Microscopy - Yanwei Zhang; Cong Luo; Hongwei Wang; Song Lang; Yan Gong; Yuguo Tang (IEEE Photonics Journal, 2017)
Structured illumination microscopy (SIM) is a widefield super-resolution technique in fluorescent imaging. For an artifact-free reconstruction, some crucial parameters should be known with high accuracy. However, the initial phase and modulation factor of illumination pattern cannot be guaranteed with enough precision experimentally, so they have to be retrieved from the acquired data. We propose a fast and robust method to compute these two parameters and then the coefficients of frequency components can be normalized. We analyze the performance of this method using simulated data and experimental data. The results demonstrate that the coefficients normalization has important effect on the improvement of reconstruction image. Compared with widefield resolution (216 nm), the lateral resolution of SIM can achieve 97 nm.